2005
DOI: 10.3200/gntp.166.4.451-466
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Processes in the Reflective-Impulsive Cognitive Style

Abstract: In this study, the authors improved the understanding of the cognitive processes underlying the reflective-impulsive cognitive style (RI), which was initially measured by J. Kagan, B. L. Rosman, D. Day, J. Albert, and W. Phillips (1964) on the Matching Familiar Figures Test (MFFT). The authors determined the relationships between the RI style and the cognitive factors, which would be likely to explain different MFFT solving modes-field dependence or independence as a cognitive style, the g factor, the spatial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
34
0
27

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(70 citation statements)
references
References 27 publications
9
34
0
27
Order By: Relevance
“…Considering the relationship between field dependence/independence and impulsivity/reflectivity, it was found that field independent students were more reflective and filed dependent students were more impulsive.This is in line with findings of Campbell and Douglas (1972) and Rozencwajg and Corroyer (2005). Findings also confirmed the studies of (Feij, 1976;Loo & Townsend 1977;Massari,1975), indicating a significant positive relationship between field independent learners and their reflectiveness.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Considering the relationship between field dependence/independence and impulsivity/reflectivity, it was found that field independent students were more reflective and filed dependent students were more impulsive.This is in line with findings of Campbell and Douglas (1972) and Rozencwajg and Corroyer (2005). Findings also confirmed the studies of (Feij, 1976;Loo & Townsend 1977;Massari,1975), indicating a significant positive relationship between field independent learners and their reflectiveness.…”
Section: Discussionsupporting
confidence: 81%
“…Gargiulo (1982) also found a significant positive relationship between field independency and reflectivity. In another study, Rozencwajg and Corroyer (2005) found that fast-accurate individuals achievedthe highest scoreson the GEFT, and reflective individuals (slow-accurate) achieved higher scores than impulsive learners (fast-inaccurate).…”
Section: Literature Review Field Dependence/independencementioning
confidence: 99%
See 1 more Smart Citation
“…Berikutnya subjek dapat melaksanakan rencana dan merumuskan jawaban dengan baik. Hal ini sesuai dengan pendapat Ancilotti (Rozencwajk dan Corroyer, 2005) yang menemukan bahwa anak yang reflektif cenderung memproses secara analitik.…”
Section: Metakognisi Subjek Bergaya Kognitif Reflektif Pada Pemecahanunclassified
“…Rumusan jawaban yang tepat dapat dibuat berdasarkan pada interpretasi hasil perhitungan dengan hati-hati sebelum mengambil keputusan, dan kemudian subjek memantapkan keyakinannya. Hal ini sesuai dengan pendapat Rozencwajk dan Corroyer (2005), yang mengatakan bahwa anak yang reflektif memperhatikan semua kemungkinan pilihan dengan hati-hati sebelum mengambil keputusan.…”
Section: Metakognisi Subjek Bergaya Kognitif Reflektif Pada Pemecahanunclassified